Disaster-Induced Resettlements: the Resilience Of Flood-Affected Households In Dar Es Salaam, Tanzania - Regina John (Geography, Environment, Sustainability)
Floods are increasingly affecting cities around the world. As a result, displacement and resettlement of floodaffected households have become the norm in many parts of the world. While resettlement may be necessary to address flood vulnerabilities, including protecting the lives of those affected, empirical studies on the post-resettlement well-being of the resettled population are scarce. This paper presents empirical findings on the livelihood situation of flood-resettled households in Dar es Salaam. The results are based on key informant and household interviews and focus group discussions with resettled households. The findings show that the resettlement area’s location in the peri-urban of the city resulted in various challenges, including inaccessibility to basic facilities and high transportation costs, with households spending an average of TZS 2,000 (~US$1) to reach a public transportation facility, i.e., a bus stand. Resettled households also have lower income levels ranging from less than TZS 50,000 (12%) to between TZS 50,000 and TZS 500, 000 (75%). While weak social ties, a lack of trust among household members, and the social stress of loss of privacy were typical challenges among resettled households, vulnerable groups, particularly women and children, were exposed to increased vulnerability. The observed post-resettlement livelihood situation is influenced by the pre-resettlement conditions of the households, characterized by large household sizes ranging from 5 to 6 members (55%) to more than seven members (35%), low education levels (77%), and informal employment, largely petty trading (56%). The paper suggests that when resettling flood-affected households, the context-specific characteristics of the affected population, such as demographic and socio-economic characteristics, and their needs, be considered to improve post-resettlement livelihood sustainability.